Uji Efek Ekstrak Etanol Herba Ketumbar (Coriandrum sativum L.) Sebagai Afrodisiak Terhadap Tikus Putih Jantan Galur Wistar (Rattus norvegicus) - Wirasti, Wirasti; Anjani, Lestari Dwi; Waznah, Urmatul; Wahyu Permadi, Yulian (Universitas Bhakti Kencana, 2025)
One of the common male sexual disorders is low libido (sexual desire). An alternative approach to overcome this problem is the use of aphrodisiacs, substances that stimulate and enhance sexual desire. Coriander (Coriandrum sativum L.) contains flavonoids, alkaloids, saponins, and terpenoids, which may improve blood circulation and potentially enhance sexual activity. This study aimed to evaluate the aphrodisiac activity of ethanolic extract of coriander herb (EHC) on the libido of male Wistar rats (Rattus norvegicus). The extract was obtained using the maceration method, while the aphrodisiac test was conducted on 25 male and 25 female rats aged 2–2.5 months with body weight ranging from 150–200 g. The animals were divided into five groups, each consisting of 5 males and 5 females: negative control (1% Na CMC), positive control (sildenafil 50 mg), and three treatment groups receiving EHC at doses of 400 mg/kgBW, 600 mg/kgBW, and 800 mg/kgBW. For five consecutive days (6:00 p.m.–7:00 a.m.), one male and one female were placed in the same cage, and sexual activities of male rats (introducing and mounting) were observed using CCTV recordings. The results showed that EHC exhibited aphrodisiac activity at a dose of 800 mg/kgBW, which was not significantly different from the positive control (sildenafil 50 mg) (p=0.571). Statistical analysis using One-Way ANOVA indicated a significant difference among groups (p<0.05), and Tukey’s post-hoc test confirmed significant differences among all EHC dose groups (p<0.05). In conclusion, the ethanolic extract of coriander herb demonstrates potential as an aphrodisiac to enhance libido in male Wistar rats.